Camino de Santiago - Škrlj, Monika (Etnolog. Nova vrsta (Ljubljana), 2020)
The article addresses Camino de Santiago pilgrimage route and the associated pilgrimage center of Santiago de Compostela which is situated in the northwest of modern-day Spain. The author deals with the historical changes to which the pilgrimage route was subjected with different intensity throughout its existence and focuses on its heritagisation in the frame of European cultural policy. Namely, the latter initiated the transformation of this ancient Roman Catholic tradition into one of the most promising identifiers of political and cultural space in contemporary Europe.
Keywords: Camino de Santiago; dediščina; Evropa; romanja